Finite Element Analysis of a Portable Bamboo Girder Used in Emergency Responses - Musthaffa A.A.; Nor N.M.; Alhayek A.; Yusof M.A.; Yaakob M.Y. (Universiti Putra Malaysia Press, 2025)
This study uses numerical simulation to explore the performance of a portable bamboo girder designed for emergency scenarios and compares it to its steel counterpart. It underscores bamboo?s appeal, offering a lightweight, quickly deployable, and eco-friendly alternative to steel. The research aims to assess bamboo?s viability in emergency bridge construction, utilising SOLIDWORKS and ANSYS to create and simulate bamboo and steel girders. A bamboo girder aimed at humanitarian assistance and disaster relief (HADR) operations was analysed through ANSYS software under a Toyota Hilux truck?s weight. Material properties, loads, and boundary conditions were defined for an accurate simulation. Three individual bamboo culms were tested in four-point flexural experiments, and the results revealed a modulus of elasticity of 14583 MPa and a local failure due to crushing and splitting with an ultimate strength of 263 MPa. Finite element analysis results indicated that the bamboo girder had a stress of 85.56 MPa and a deflection of 84.68 mm. Although the steel girder showed lower deflection, it had significantly higher stresses and weighed 180% more than the bamboo version. The bamboo girder?s deflection surpassed the recommended limit under a fully loaded truck, indicating room for improvement. However, stress analysis revealed that the bamboo?s structural integrity remained below its design strength. Conversely, the steel girder exhibited higher stresses and considerably greater weight. Despite deflection concerns, the bamboo girder demonstrated structural soundness and lower weight compared to steel. This positions it as a viable solution for swift emergency deployment, warranting further refinement for enhanced performance. ? Universiti Putra Malaysia Press.